Overview of Adolescent Mental Health at SMP 1 Wanasari Brebes - Muhammad Aljaz Pra Aditya; Siti Nurjanah (Proceedings Series on Health & Medical Sciences, 2026)
Adolescents are vulnerable to mental health disorders as adolescence is a transitional period from childhood to adulthood, marked by socio-physiological growth and development. Adolescence is considered a volatile and vulnerable time because adolescents undergo significant changes during this period, both physically, psychologically, and emotionally. The objective of this study was to describe the mental health of adolescents at SMP 1 Wanasari Brebes. The research method used was descriptive analytic with data collection through the SDQ questionnaire. The study sample consisted of 82 respondents from SMP 1 Wanasari Brebes, and cluster random sampling was employed. Data were analyzed using univariate analysis with frequency percentages. The overview of adolescent mental health at SMP 1 Wanasari Brebes showed that the emotional category for most respondents was within the normal range (50%), behavior was predominantly normal (49%), hyperactivity was mostly normal (82%), peer relations were mostly borderline (38%), and prosocial behavior was predominantly normal (85%). The total difficulty score was mostly in the borderline category (46%). The mental health overview of adolescents indicates a normal scale in the emotional, behavioral, hyperactivity, and prosocial categories. The borderline scale was observed in the peer relations category and total difficulty score.